Chemotaxonomic profiling of fungal endophytes of Solanum mauritianum (alien weed) using gas chromatography high resolution time-of-flight mass spectrometry (GC-HRTOF-MS) - Pelo, Sharon Pauline; Adebo, Oluwafemi Ayodeji; Green, Ezekiel (Metabolomics, 2021)
Introduction Since ancient times medicinal plants have been used as medicine in many parts of the world to promote human health and longevity. In recent years many novel secondary metabolites of plants have been isolated and reported to provide lead compounds for new drug discoveries. Solanum mauritianum Scopoli is native to South America. It is reported to be used by native South Americans during famine as a vegetable and as medicine to cure various diseases. In South Africa the plant is viewed as weed and is facing eradication, however, this plant is a valuable subject for research into its potential pharmaceutical and chemical uses. This study elucidated the metabolic profile of fungal endophytes that have promising bioactive secondary metabolites against pathogenic microorganisms, including mycobacterium species. Material and methods Fungal endophytes from a weed Solanum mauritianum Scop. were used to synthesize secondary metabolites. Gas chromatograph high-resolution time-of-flight mass spectrometry (GC-HRTOF-MS) was used to analyse volatile compounds to prove that potentially fungal endophytes could be extracted from this weed. Extracts obtained with ethyl acetate were screened for phytochemicals and analyzed using a gas chromatograph high-resolution time-of-flight mass spectrometry system. Principal component analysis was used to compare the gas chromatograph high-resolution time-of-flight mass spectrometry data for differences/similarities in their clustering. Phytochemical screening was conducted on the crude extracts of fungal endophytes obtained from different parts of Solanum mauritianum Scopoli (leaves, ripe fruit, unripe fruit and stems). Results Phytochemical screening indicated the presents of alkaloids, flavonoids, glycosides, phenols, quinones and saponins. Quinones were not present in the crude extracts of Fusarium sp. A total of 991 compounds were observed in the fungal endophytes, and Cladosporium sp. (23.8%) had the highest number of compounds, compared to Paracamarosporium leucadendri (1.7%) and Talaromyces sp . (1.5%). Some volatile compounds such as eicosane, 2-pentadecanone, 2-methyloctacosane, hexacosane and tridecanoic acid methyl ester with antibacterial activity were also observed. Conclusion Compositional variations between the plant and fungal endophyte phytochemicals were observed. The results of this study indicate that fungal endophytes from Solanum mauritianum Scop. contain compounds that can be exploited for numerous pharmaceutical and medicinal applications.